ITALIAN RESEARCH ON MEDITERRANEAN OPHIOLITES: SELECTED CONTRIBUTIONS (Ofioliti, 2004)
The Mediterranean area represents a composite geological puzzle where several different sized microplates are interposed between the two main plates of Eurasia and Africa. These microplates, consisting of both continental and oceanic lithosphere, have been involved in a long-lasting geodynamic history since Early Triassic, the reconstruction of which is still matter of debate. Useful constraints for the geodynamic evolution are provided by the study of the on-land remnants of the oceanic lithosphere, i.e. ophiolites, presently preserved in the Alpine collisional belts throughout the whole Mediterranean area. The rifting and opening of the oceanic basins, the generation of new lithosphere above intra-oceanic subduction zones, as well as the subsequent closure processes, can be fully investigated by studying ophiolites with different approaches, including petrology, geochemistry, tectonics, stratigraphy, and structural geology. The study of Mediterranean ophiolites is also particularly relevant for providing important constraints for the knowledge of mantle and crustal processes active in modern oceanic lithosphere. The explorations of the present-day oceanic crust, as well as the three-dimensional relationships among different rock units, can be greatly improved by the observation of the internal architecture of well-preserved ophiolite sequences. The G.L.O.M. Ð Gruppo di Lavoro sulle Ofioliti Mediterranee (Working Group on Mediterranean ophiolites), composed of Italian researchers having distinct scientific background, has been devoted to the study of the ophiolites in the Mediterranean area since the 70s. G.L.O.M. has been heading the IGCP Projects n. 195 (1982-1986) and n. 256 (1988-1992) on ophiolite genesis and evolution of oceanic lithosphere. Its activity is mainly supported by M.I.U.R. (Ministry of Education, University and Scientific Research) and CNR (National Research Council). In the last years, different teams of Italian researchers have been involved in the studies of ophiolitic sequences from Dinaric-Hellenic and Alpine-Apennine belts, providing a great amount of geological, petrological, geochemical and structural data to the international scientific community. This volume of OFIOLITI includes some selected papers on Mediterranean ophiolites, concerning both original updated syntheses of ongoing research projects and reviews of previous works. This volume will be issued for the 32nd International Geological Congress Ð Florence 2004 with the aim to present the current knowledge resulting from the Italian research on Mediterranean ophiolites.Beccaluva LuigiBortolotti ValerioMarroni MichelePandolfi LucaPiccardo Giovanni B.Saccani EmilioTribuzio Riccardo